2016
DOI: 10.21451/1984-3143-ar726
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of fruit-juices on sperm viability of West African Dwarf goat bucks during cryopreservation

Abstract: The present study was conducted to determine the effects of adding fruit-juices to semen extenders on viability of buck spermatozoa during cryopreservation in two studies. Pooled semen samples obtained from West African Dwarf (WAD) goat bucks were diluted with Tris-egg yolk based extenders. In study I, the diluted semen samples were supplemented with orange (Citrus sinensis), cucumber (Cucumis sativus) and pineapple (Ananas comosus) juices (2.5, 5, 7.5 and 10 ml/100 ml). In study II, the diluted semen samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
2
5
1
1
Order By: Relevance
“…Similarly, Tvrda et al (2017) suggest that lycopene supplemented to the semen extender acts as an effective motion-promoting and membrane protecting molecule, significantly improving sperm motility, membrane integrity, and mitochondrial activity during preservation. In agreement with this study is the report of Daramola et al (2016) that supplementing extenders with fruit juice (orange and pineapple) at 10% consistently improved motility, acrosome integrity and membrane integrity, and reduced sperm abnormality. The improvement in semen quality could be attributed to the presence of substances in these fruits such as vitamins and phenolic compounds are known to function as antioxidants (Kiwon et al 2003;Cutler et al, 2008).…”
Section: Quality and Fertility Of Rabbit Semen Diluted With Watermelosupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, Tvrda et al (2017) suggest that lycopene supplemented to the semen extender acts as an effective motion-promoting and membrane protecting molecule, significantly improving sperm motility, membrane integrity, and mitochondrial activity during preservation. In agreement with this study is the report of Daramola et al (2016) that supplementing extenders with fruit juice (orange and pineapple) at 10% consistently improved motility, acrosome integrity and membrane integrity, and reduced sperm abnormality. The improvement in semen quality could be attributed to the presence of substances in these fruits such as vitamins and phenolic compounds are known to function as antioxidants (Kiwon et al 2003;Cutler et al, 2008).…”
Section: Quality and Fertility Of Rabbit Semen Diluted With Watermelosupporting
confidence: 92%
“…The improvement in semen quality could be attributed to the presence of substances in these fruits such as vitamins and phenolic compounds are known to function as antioxidants (Kiwon et al 2003;Cutler et al, 2008). Gardner et al (2000) had earlier reported that concentrations of vitamin and total phenolic contents in fruit-juices have a strong relationship with antioxidant capacity (Daramola et al 2016). Similarly, Amedu and Idoko (2016) reported that Citrullus lanatus promotes normal sperm morphology, sperm concentration, sperm volume and sperm motility in rat semen, probably due to the antioxidant activity of lycopene present, similar reports also corroborates this claims in chilled or frozen rabbit, turkey and fowl semen (Rosato et al 2012).…”
Section: Quality and Fertility Of Rabbit Semen Diluted With Watermelosupporting
confidence: 55%
“…Vitamins A, C and E have been shown to be potent antioxidants (Breininger et al, 2005;Ondei et al, 2009). The inclusion of fruit juices from orange (Citrus sinensis), cucumber (Cucumis sativus) and pineapple (Ananas comosus) as constituents of semen extenders has recently been proved to improve the quality of stored spermatozoa (Daramola et al, 2016). Apple (Malus domestica) and orange (Citrus sinensis) are antioxidantrich fruits with high levels of these vitamins (Cutler et al, 2008) that probably outweigh other food nutrients in reducing the effect damage by reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…Van Vuren and Steyn (2017) [25] noted however that the level, type, concentration, temperature, and exposure period of the fruit juice function to evaluate the quality and viability of the milt. Fruit antioxidants include carotenoids, vitamins, phenolic compounds and flavonoids and have proved to function as singlet and triplet oxygen quenchers, free radical scavengers and peroxide decomposers (Anghel et al, 2010;Daramola et al, 2016;) [6,9,10] . Preservation of fish milt has become an uphill task due to the fact that most artificial cryo-protectants in use have oxidative impact on fish milt spermatozoa.…”
Section: Discussionmentioning
confidence: 99%